A few days ago
Nathaniel

# Change (2x+1)(x+5) to expanded form? Help?

Can you please change (2x+1)(x+5) to expanded form. And possibly explain how you knew what to do? Thanks 😀

A few days ago
Olivia!

In this situation we will use the “FOIL” method to arrived at the expanded form.

F= front

O= outside

I= inside

L= Last

(2x+1)(x+5)

So first we multiply the “front” 2 numbers of each form. so:

2X x X = 2x^2 (squared)

Then we multiply the “outside” numbers:

2X x 5 = 10x

Next we multiply the “inside” numbers:

1 x X= x

And finally we multiply the “last” numbers:

1 x 5 =5

So now we add all the number up combining like forms:

2x^2 + 10x + x + 5 =

Lastly we arrived at:

2x^2 + 11x + 5 for our answer!

Hope this helped! ^.^ Contact me if you have anymore questions.

0

A few days ago
kai
2x(squared)+11x+5.

you multiply each element of each individual equation by every other. so do everything: 2x * x, 2x * 5, 1 * x and 1 * 5. when you put all the results together, you’ll get 2x(squared) + 10x + x +5. 10x and x have the same variable, so put them together.

0